A Study on Automatic Tuning of PID Governor for Marine Diesel Engine - Ohtsu, Kohei; Okazaki, Tadatsugi; Hotta, Toshiyuki; Nakatani, Toshihiko (JOURNAL OF THE MARINE ENGINEERING SOCIETY IN JAPAN, 1997)
The most of governors for marine diesel engine is still designed based on the classical PID control theory. Various methods have been proposed for tuning PID parameters. One of the conventional methods often used in the gain tuning is the Ziegler Nichols ultimate method. There are some problems, however, when this conventional method is apllied to operating marine diesel engine as follows; 1) It is not always safe technique because a proportional gain in this method is gradually increased until the system reaches a critical state. 2) The success of the technique depends largely on operator's experience. To solve these problems, it is neccesary to adopt some automatic gain tuning technique, which does not give great influences on the system and can be easily implemented without danger. In this paper, a simple and a safe automatic gain tuning method using relay control is provided for diesel engine governor system with PID control law. In this method, a limit cycle with small amplitude is occurred, at the beginning, through a fuel oil pump rack, and then the amplitude and the period of the limit cycle are observed. Since the two quantities obtained under such limit cycle equivalently correspond to those by the Ziegler Nichols ultimate method, these are utilizable as the parameters for obtaining the optimal gains recommended by Ziegler Nichols. This technique is applied to the governor system of a small training ship, full scale experiments were carried out and the results of the experiments are discussed.